Evolution and Tendencies of the Petro-Rentier State in Ecuador 2001-2010 - Bäckström, Caroline (Papeles de Europa, 2014)
A rentier state is characterized by having a non-diversified economic structure that is biased towards petroleum, high representation of oil income in total public income, rent management ruled by political criteria and high economic vulnerability to changes in oil prices. This paper concludes that these characteristics in Ecuador were intensified as a consequence of the political change in 2007. Particularly features related to the public sector and the objectives of rent management where deepened, but the vulnerability of demand to fluctuations in oil prices did also increase. So, in spite of the government’s efforts to increase non-oil income and invest in capital, a higher level of rentierism has not been counteracted.